Praktik Gala Tanah Sawah di Desa Meunasah Meucat dalam Persepektif Mazhab Syafi’i - muhammad Rizqan Finan (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Gala is a mention of a pledge in Aceh language which is a tradition that has been handed down in Meunasah Meucat village. In the form of agreements Gala, both of pledgor and pledgee are agree that the pledgor is a person who utilize the paddy soil as a pledge, with the condition that pledgor pays the rent (giving a percentage of the crop) to pledgee during contract of Gala took place, it means until pledgor repay his debt. This research was written to know the process of gala in Meunasah Meucat and also to know Imam Syafi’i’s fatwa about it. This research is empirical research with conceptual approach. Most of the primary data in this research was obtained from the interview. While secondary data obtained from the literature. From the research that has been done, scholars of Shafi said pledgor allowed to utilize pledge long as it is not detrimental and causing unfavorable to pledgee. In case of the requirement of rent payment (giving a percentage of the crop) by pledgor to pledgee, scholars of Shafi said that if in the contract loans payable, pledgee requires something that is detrimental to the pledgor, as things produced by pledge or utilization of pledge is for pledgee, then the requirement is not legitimate and in more powerful opinion the contract of pledge also becomes invalid.